2021
DOI: 10.3390/ijms22169066
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Ghrelin to the Pathogenesis of Growth Hormone Deficiency

Abstract: In this review we described the interactions between ghrelin and the growth hormone (GH)-insulin-like growth factor 1 (IGF-1) axis in children and adults with growth hormone deficiency (GHD). A possible involvement of these interactions in the pathogenesis of unexplained cases of GHD was suggested. Current research provides more and more details to the knowledge on the circadian rhythm of ghrelin. We gathered reports on the decreasing effect of Helicobacter pylori-related chronic gastritis on the number of ghr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 118 publications
0
15
0
Order By: Relevance
“…We did not measure ghrelin levels, but in this case we hypothesize that it is elevated at the peak of EAE, as ghrelin levels also increase after food deprivation and after many forms of weight loss [ 45 ], as shown here in EAE. It has been proposed that ghrelin decreases plasma levels of IGF-1 and thus inhibits the negative effect of IGF-1 on GH secretion and acts directly on somatotrophs [ 44 , 46 ], which seems plausible in our experimental model. In addition, acute inflammation with subsequent weight loss leads to a negative energy balance, whereby ghrelin can influence the orexigenic centers in the hypothalamus to conserve energy.…”
Section: Discussionmentioning
confidence: 66%
“…We did not measure ghrelin levels, but in this case we hypothesize that it is elevated at the peak of EAE, as ghrelin levels also increase after food deprivation and after many forms of weight loss [ 45 ], as shown here in EAE. It has been proposed that ghrelin decreases plasma levels of IGF-1 and thus inhibits the negative effect of IGF-1 on GH secretion and acts directly on somatotrophs [ 44 , 46 ], which seems plausible in our experimental model. In addition, acute inflammation with subsequent weight loss leads to a negative energy balance, whereby ghrelin can influence the orexigenic centers in the hypothalamus to conserve energy.…”
Section: Discussionmentioning
confidence: 66%
“…A major limitation of animal models is that they cannot self‐report hunger or other physiological sensations that would inform mechanistic work. Since ghrelin was first described and noted as a growth hormone secretagogue receptor (GHS‐R) agonist (Kojima et al, 1999 ), much study has focused on the effects on hunger and appetite regulation along with other aspects of energy balance (Bouillon‐Minois et al, 2021 ; Lewiński et al, 2021 ; Ouerghi et al, 2021 ).…”
Section: Introduction Results and Discussionmentioning
confidence: 99%
“…Additionally, the concentration of vitamin D depends on the dietary intake; unfortunately, geriatric patients often develop nutritional disorders, and patients are often malnourished and experiencing the ‘anorexia of aging’ [ 20 ]. Ghrelin is a peptide hormone that plays a key role in the neurohormonal regulation of food intake (stimulates appetite), energy homeostasis, and growth hormone (GH) secretion [ 21 ]. In our study, along with a lower concentration of vitamin D, we also observed a lower concentration of ghrelin.…”
Section: Discussionmentioning
confidence: 99%